Membangun Fondasi Bangsa yang Cerdas Melalui Gerakan Literasi Nasional - Misra Nova Dayantri; Muhammad Irwan Padli Nasution (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Data from PISA (2012) in the Assessment Framework shows that the science and maths literacy of Indonesian children, aged 15, is ranked 38th out of 40 participating countries. Maths literacy ranked 50th out of 57 countries, and science literacy also ranked 50th out of 57 countries. Data from the Progress in International Reading Literacy Study shows that the reading ability of grade IV primary school children in Indonesia is ranked 41st out of 45 countries, both developed and developing countries. The results of the Indonesian Students Competency Assessment (AKSI) or the Indonesia National Assessment Program (INAP) also show that most students are deficient in maths, reading and science: around 77.13% of students are deficient in maths, 46.83% are deficient in reading and 73.61% are deficient in science. This points to the need to improve the quality of education in Indonesia through the development of effective teaching methods, curriculum improvement, teacher quality improvement, and wider access to quality education. The Ministry of Education and Culture (MoEC) responded by launching the National Literacy Movement (GLN) programme, which includes the School Literacy Movement, the Reading Indonesia Movement and the Family Literacy Movement. This journal uses a library research method with a qualitative approach, analysing data from relevant journals and books. Literacy is an essential life skill that enables individuals to function optimally in society through critical thinking. Cultural literacy is important for the future of the nation, influencing the nation's intelligence and knowledge, which comes from written and spoken information. The National Literacy Movement guidelines cover six dimensions of literacy: literacy in reading and writing, numeracy, science, digital, financial, and cultural and civic literacy. GLN is developed through three domains: family, school and community. Evaluation and assessment of GLN is necessary to improve and appreciate the success of the programme. The principles of GLN are sustainability, integration, and involvement of all stakeholders. As an effort to educate the nation, GLN involves all Indonesian citizens to improve their understanding, knowledge and skills needed in the 21st century.